Multi-Targeted Approach to Treatment of Cancer - Gandhi, Varsha; Mehta, Kapil; Grover, Rajesh; Pathak, Sen; Aggarwal, Bharat B. (Springer International Publishing : Imprint: Adis, 2015)
In this book, clinicians and basic scientists from USA, India, and other countries discuss the rationales and clinical experiences with targeted approaches to treat, prevent, or manage cancer. Cancer is a hyperproliferative disorder that is regulated by multiple genes and multiple cell signaling pathways. Genomics, proteomics, and metabolomics have revealed that dysregulation of dozens of genes and their products occur in any given cell type that ultimately leads to cancer. These discoveries are providing unprecedented opportunities to tackle cancer by multi-faceted approaches that target these underpinnings. This book emphasizes a multi-targeted approach to treating cancer, the focus of the 5th International Conference on Translational Cancer Research that was held in Vigyan Bhawan, Delhi (India) from Feb 6-9, 2014.